Improving Quality Control Process Through Value Stream Mapping - Fitri Ikatrinasari, Zulfa; Kosasih, Dan (International Journal of Engineering and Technology, 2018)
PT. AEMI is one of the growing electronic component manufacturing company. By this time, Kaizen project has been run and managed to become a culture in PT AEMI. However, the project has not integrated, comprehensive and not yet has a long-term goals. Implementation of value stream mapping (VSM) in PT AEMI is expected to make Kaizen projects more focused and to produce increasing of the maximum efficiency. In addition, VSM Kaizen is believed to make the those programs more integrated, effective and comprehensive. This study aims to: (1) create a current state mapping in the Department of Quality Control PT. AEMI, (2) identify wastes in the Department of Quality Control PT.AEMI, (3) create a future state mapping at the Department of Quality Control PT. AEMI, (4) make a plan of improvement and analyzing the application. Stages of the study were as follows: (1) identification of work processes, (2) collect and analysis of work process time, (3) analysis of the current state mapping, (4) calculate of lead time and process time, (5) analysis of value added and non value-added activities, (6) analysis of wastes, (7) make a plan of future state mapping, (8) improvement design (improvement planning), (9) implementation of improvement, (10) analysis of the implementation of improvements. The results of this study are: 1) current state mapping at QC Department shows that the total lead time of 848 minutes where there is non-value added activity of 778 minutes. 2) identify waste on the handling process where the product movement from assembly to QC for 2 minutes, movement transactions from assembly to QC for 479 minutes and the waiting time atÂ inspection area for 727 minutes. 3) future state mapping at QC Department shows that the total lead time of 516.5 minutes where there is non-value added activity of 446.5 minutes. 4) the improvement to do is to change the lay out where final inspection is moved from QC to manufacturing so as to result in reduce of non-value added activity by 46%.Â